Women Empowerment for Poverty and Inequality Reduction in Sudan - Osman, Eiman; Etang, Alvin; Kirkwood, Daniel (World Bank, Washington, DC, 2021)
Several key gender issues likely act as an impediment to poverty reduction and shared prosperity in Sudan. While many of these issues are common across countries in the Sub-Saharan Africa region, some of them are accentuated by the status of Sudan as a fragile state. Fragility and conflict negatively affect men and women in different ways, resulting in gender-specific disadvantages. While men are often disproportionately affected by the direct effects of conflict (for example, death and disability), women and girls are affected by a range of constraints and protection challenges that fragility and conflict pose. These issues include disrupted access to basic social services and infrastructure, lower access to productive assets, displacement, and increased exposure to gender-based violence (GBV). This study aims to examine how gender equality has evolved in Sudan during the last decade, by looking at different dimensions. These include the accumulation of endowment in all its forms (human capital [education and health] and physical capital), access to economic opportunities (labor market opportunities and access to income-generating activities), access to services (water, sanitation, and electricity), and voice/representation to make decision at all levels. The study will highlight the areas in which gender inequality persists and propose policies to reduce gender inequality in Sudan.